Analisis Hubungan Kausalitas Antara Kurs dengan Inflasi Di Indonesia (2011.I - 2016.VI) - , Rinawati; , Eni Setyowati, SE, M.Si (2017)
Economic fundamentals that one exchange is dominant for review. The exchange rate has also fluctuated linkages with the real sector, in this case the phenomenon of fluctuating exchange rates affect inflation directly affects vice versa. This study aims to analyze the causality the exchange rate and the inflation rate. This study uses data bulana the period January 2011 - Juni 2016, the data obtained from Bank Indonesia (BI). Analysis tools using Granger causality test to determine the causal relationship. Granger causality test research results show exchange rate with inflation there have also been a one-way causality. Based on this research by Bank Indonesia should be able to control the optimal exchange rate volatility in order to achieve price stability and investment . Also the need for the government's role to assist the central bank in an effort to control the exchange rate that maintained stable economic fundamentals and strong.